GANDAPURA : PENGOLAHAN, FITOKIMIA, MINYAK ATSIRI DAN DAYA HERBISIDA - Hernani Hernani (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
Gandapura (Gaultheria fragrantissima) is a plant with high potency to develop because its main compound, methyl salicylate, is widely used in food and beverages, pharmaceutical and cosmetics industries. Present work was to study the processing, phytochemistry, essential oil content and herbicide effect from extracts and essential oils of gandapura. For the processing of raw material the wilting method was used (2,3 and 5 days) to observe its effect on essential oil and methy salicylate, quality of raw material such as ash content, ash insoluble in acid, extractives soluble in water and alcohol. The phytochemistry was conducted by the MMI method. The extract was made by the use of 3 types of solvent, such as methanol, ethyl acetate and hexane. The herbicide effect was conducted in vitro, using a modification method of Milliskiemiez et al. (1992) and Nezu et al. (1996). The result of the processing method showed that the longer the wilting time, the lower essential oil contents. However, methyl salicylate content was still constant in 2 days wilting time and decreased until 80% after 532 days. The water and alcohol soluble extractives were very high. The phytochemistry showed that methanol and ethyl acetate extracts contained alkaloid, flavonoida, glycoside, saponin and tannin while the hexane extract contained glycoside and alkaloid. The herbicide in vitro test on M. invisa showed that extracts and essential oil of gandapura inhibit the growth of shoots ranging from 42 - 70%, 36666,88 – 80,55%, 24,80 - 100% and 99,67%, each for methanol, ethyl acetate, hexane, essential oil and synthetic essential oil, respectively. The abundances of methyl soliveylate, as of the main compound, reashes 97%, while the methanol extract contain only 3,66%.